Effect of Learning Using Digital Student Worksheets Assisted by Canva on the Writing Anecdotal Texts Skills - Edwin Samosir; Martua Reynhat Sitanggang Gusar; Juni Agus Simaremare (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe: 1) pre-test results of anecdotal text writing skills; 2) prost-test results of anecdotal text writing skills after participating in learning using digital student worksheets assisted by Canva media; 3) the effect of using Canva-based digital student worksheets on anecdotal text writing skills. This study uses a descriptive-quantitative method through a one-group pretest-posttest design which took place in the odd semester of the 2025/2026 academic year in class X of SMA Negeri 1 Tanjung Morawa. The population was the students of class XI of SMA Negeri 1 Tanjung Morawa who participated in the pre-test of writing anecdotal texts, participated in learning the ability to write anecdotal texts using digital student worksheets assisted by Canva media, and finally took the post-test. They numbered 36 students. Based on Slavin's formula, a sample of 32 students was determined; selected by simple random sampling with a technique without replacement. Pre-test and post-test data on the ability to write anecdotal texts were collected using a performance test instrument with a take-home examination system. Data analysis was carried out using inferential statistics, namely one-sample t-test and paired sample t-test after the normality test and homogeneity test were fulfilled. The checklist is used to validate the results of the pre-test and post-test data scoring. Research results: 1) the pre-test results of anecdotal text writing skills are in the low category; the mean observation of 16.85 (60.19) turns out to be the same as the mean expectation of 17.36 which is equivalent to a standard score of 62.00 percent; 2) the post-test results of anecdotal text writing skills are in the high category; the mean observation of 22.06 (78.78) turns out to be the same as the mean expectation of 22.40 (80.00); 3) Canva-assisted digital student worksheets is proven to have a significant effect on anecdotal text writing skills.